Genos Eros Thanatas - Boatto, Alberto; Galleria de'Foscherari, Bologna (Bologna : Edizioni Galleria de' Foscherari, 1974)
Burri, ALberto ; Kounellis, Jannis ; Cintoli, Claudio ; Pascali, Pino ; Boetti, Alighiero ; Pisani, Vettor ; Fioroni, Giosetta ; Fabro, Lucio ; Mauri, Fabio ; etc.
Genos Eros Thanatos, Galleria de'Foscherari, Bologna, 1974
boek